1999
DOI: 10.1016/s0370-2693(99)01291-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting heavy charged Higgs bosons at the LHC with triple b-tagging

Abstract: We investigate the charged Higgs boson signal at the LHC using its dominant production and decay modes with triple b-tagging, i.e. tH − → ttb → bbbW + W − , followed by leptonic decay of one W and hadronic decay of the other. We consider the continuum background from the associated production of tt with a b-or a light quark or gluon jet, which can be mis-tagged as b-jet. We reconstruct the top quark masses to identify the 3rd b-jet accompanying the tt pair, and use its p T distribution to distinguish the signa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 15 publications
2
52
0
Order By: Relevance
“…Figure 7 shows this invariant mass distribution for the signal along with the above mentioned background processes for different H ± masses at tan β = 40 Similar results hold for tan β ≃ 1.5. One can check that the significance level of the signal is S/ √ B > ∼ 5 [25]. The corresponding H ± discovery reaches in the high and low tan β regions are shown in Fig.…”
Section: Search In the Tb Channelmentioning
confidence: 85%
See 1 more Smart Citation
“…Figure 7 shows this invariant mass distribution for the signal along with the above mentioned background processes for different H ± masses at tan β = 40 Similar results hold for tan β ≃ 1.5. One can check that the significance level of the signal is S/ √ B > ∼ 5 [25]. The corresponding H ± discovery reaches in the high and low tan β regions are shown in Fig.…”
Section: Search In the Tb Channelmentioning
confidence: 85%
“…One requires leptonic decay of one of the tt pair and hadronic decay of the other with a p T > 30 GeV cut on all the jets [25]. For this cut the b-tagging efficiency at LHC is expected to be ∼ 50%.…”
Section: Search In the Tb Channelmentioning
confidence: 99%
“…However, in refs. [26][27][28] it has been demonstrated that the H + → tb signature can lead to a visible signal at the LHC provided that the charged Higgs mass is below 600 GeV and tan β is either below 1.5 or above 40. An alternative decay mode to detect a heavy charged Higgs boson is H ± → τ ν [29,30], even if such a decay is suppressed for heavy charged Higgs bosons, it has the advantage of being much cleaner than H + → tb.…”
Section: Jhep05(2016)093mentioning
confidence: 99%
“…There will instead be associated production of tH ± , which can be described either in a five-flavor scheme (5FS) as due to bg → tH ± , or as gg → tbH + (4FS). The two processes require proper matching [22], for which the Monte Carlo (MC) implementation MATCHIG [23] is available. The QCD corrections to tH ± production are known both in the 5FS [24], and the 4FS [25].…”
Section: Mc@nlo For Charged Higgs Productionmentioning
confidence: 99%